Acoustic streaming and Sun's meridional circulation. (September 2016) - Valverde, Jose Manuel
Abstract: A vast number of physical processes involving oscillations of a bounded viscous fluid are relevantly influenced by acoustic streaming. When this happens a steady circulation of fluid develops in a thin boundary adjacent to the interface. Some examples are refracted sound waves, a fluid inside a spherical cavity undergoing torsional oscillations or a pulsating liquid droplet. Steady streaming around circular interfaces consists of a hemispherically symmetric recirculation of fluid from the equatorial plane to the polar axes closely resembling the meridional circulation pattern observed in the Sun's convection zone that determines the solar cycle. In this paper, it is argued that the acoustic pulsations exhibited by the Sun would lead to acoustic streaming in the boundary of the convection zone. A simple estimation using a typical dominant frequency of 3 mHz and the observed surface oscillation amplitude yields a steady streaming velocity u s ∼ 10 m s −1, which is on the order of the meridional circulation velocity observed in the Sun's convection zone.